The Influence of Product Quality and Service Quality on Consumer Satisfaction - Putri Rahmawati; Asri Solihat; Lindayani Lindayani (Entrepreneurship Faculty, Universitas Garut, 2025)
The culinary industry is one of the fastest-growing sectors in Indonesia and plays an important role in supporting the development of the creative economy. One traditional culinary product that remains popular is green banana. However, the rise of modern food trends and increasingly intense competition in the culinary business requires traditional food entrepreneurs to continuously innovate in order to maintain their existence. Mamayu Pisang Ijo is one of the home-based culinary businesses that focuses on product quality and service quality as its main strategies to enhance customer satisfaction and maintain customer loyalty. This study aims to determine the influence of product quality and service quality on customer satisfaction at Mamayu Pisang Ijo. The research employed a quantitative approach with a survey method. A total sample of 176 respondents was obtained using the Slovin formula, and data were collected through an online questionnaire using a Likert scale. Data analysis was conducted using SPSS through validity tests, reliability tests, multiple linear regression, t-tests, F-tests, and coefficient of determination analysis. The results show that product quality and service quality simultaneously have a significant effect on customer satisfaction, with an F-value of 120.842, which is higher than the F-table value of 2.27. In addition, the Adjusted R² value of 0.583 indicates that 58.3% of the variation in customer satisfaction can be explained by the two variables. These findings suggest that improving product and service quality is essential to maintaining customer satisfaction, suggesting that businesses like Mamayu Pisang Ijo must continue to improve the quality offered to remain competitive in the culinary industry. Moreover, this research serves as a reference for traditional culinary businesses in designing marketing strategies based on product and service quality to increase competitiveness. This study also contributes to the academic literature on consumer behavior in traditional culinary industries amid modern competition.